Emotional space. Home vs institutionalised space. Kindergarten, as a meaningful place for six-year-old children - Karczmarzyk, Malgorzata (International Journal about Parents in Education, 2023)
Why home and kindergarten, these meaningful places, are such different worlds? Why are there different meanings attached to meaningful places? And why do two places have absolutely different meaning to a six-year old child? What does the social process in the places look like, and how is this influences by ‘meaningful others’? These questions are the core of me paper. Such different spaces also: people such as ‘meaningful others’, child, his/her parents and peers make a child become a part of a society. And the way in which the space influences the child, depends on his/her socialisation process. Through the semiotic analysis of children’s drawings I am going to show how the emotional level connects with places and people, that I selected. I am going to characterise these places, that is: home and kindergarten, but also I am going to show that these places are not empty. They are full of people, who are more or less meaningful to the child.